Fermentation of DaiDai fruit and its biological activity - Meng, Xiangyu; Tang, Nan; Su, Wenfeng; Chen, Weiji; Zhang, Yue; Li, He (Frontiers in Microbiology, 2024)
DaiDai fruit, a medicinal and edible plant fruit, is abundant in biologically active compounds and has a long history of use in traditional Chinese medicine. This research focuses on utilizing fermentation to develop a functional DaiDai fruit fermentation broth. Lactobacillus, Bacillus subtilis and Saccharomyces cerevisiae were employed in the fermentation process. By conducting screenings of bacterial strains, single factor experiments, and response surface methodology, the total flavonoids, polysaccharides, polyphenols, and 1,1-diphenyl-2-trinitrophenylhydrazine (DPPH) free radical scavenging rate were used as the index for selection, ultimately identifying Lactobacillus L-13 as the optimal fermentation strain. The optimal fermentation conditions were determined to be a time of 108 h, a temperature of 43.6°C, and a solid-liquid ratio of 1:15.157 (w/v). Under these conditions, the total flavonoid content reached 412.01 mg/g, representing a 36.71% increase compared to conventional extraction methods. The contents of polysaccharides and polyphenols and the DPPH scavenging rate were also increased. The fermentation broth of DaiDai fruit exhibited inhibitory effects on tyrosinase and melanin production in mouse melanoma cells B16-F10 induced by α-MSH and anti-inflammatory properties in a zebrafish inflammation model. These indicate that the DaiDai fruit fermentation broth possesses anti-melanoma, whitening, and anti-inflammatory properties, showcasing significant potential for applications in medicine, cosmetics, and other industries.